Microwaves reduce water refractive index - Asakuma, Y; Maeda, T.; Takai, T.; Hyde, Anita; Phan, Chi; Ito, S.; Taue, S. (Nature Publishing Group, 2022)
Microwaves, long used as a convenient household appliance, have been increasingly used in industrial processes such as organic synthesis and oil processing. It has been proposed that microwaves can enhance these chemical processes via a non-thermal effect. Here we report the instantaneous effect of microwaves on the permittivity and phase velocity of light in water through the in-situ measurement of changes in refractive index. Microwave irradiation was found to reduce the water refractive index (RI) sharply. The reduction increased as a function of microwave power to a far greater extent than expected from the change in temperature. The phase velocity of light in water increases up to ~ 5% (RI of 1.27) during microwave irradiation. Upon stopping irradiation, the return to the equilibrium RI was delayed by up to 30 min. Our measurement shows that microwaves have a profound non-thermal and long-lasting effect on the properties of water. Further investigation is planned to verify if the observed RI reduction is restricted to the region near the surface or deep inside water bulk. The observation suggests a relationship between microwave-induced and the enhanced aqueous reactions.